Transcriptional reprogramming of natural killer cells by vaccinia virus shows both distinct and conserved features with mCMV - Depierreux, Delphine M.; Smith, Geoffrey L.; Ferguson, Brian J. (Frontiers in Immunology, 2023)
Natural killer (NK) cells have an established role in controlling poxvirus infection and there is a growing interest to exploit their capabilities in the context of poxvirus-based oncolytic therapy and vaccination. How NK cells recognise poxvirus-infected cells to become activated remains unclear. To address this knowledge gap, we studied the NK cell response to vaccinia virus (VACV) in vivo, using a systemic infection murine model. We found broad alterations in NK cells transcriptional activity in VACV-infected mice, consistent with both direct target cell recognition and cytokine exposure. There were also alterations in the expression levels of specific NK surface receptors (NKRs), including the Ly49 family and SLAM receptors, as well as upregulation of memory-associated NK markers. Despite the latter observation, adoptive transfer of NK memory populations did not confer protection from re-infection. Comparison with the NK cell response to murine cytomegalovirus (MCMV) infection highlighted common features, but also distinct NK transcriptional programmes initiated by VACV. Finally, there was a clear overlap between the NK transcriptional response in humans vaccinated with an attenuated VACV, modified vaccinia Ankara (MVA), demonstrating conservation between the NK response in these different host species. Overall, this study provides new data about NK cell activation, function and homeostasis during VACV infection, and may have implication for the design of VACV-based therapeutics.